Pengaruh Waktu Dan Lama Penyinaran Terhadap Tanaman Buah Naga (Hylocereus Polyrhizus) Pada Fase Generatif - Safitri, Ela; Hasibuan, Syafrizal; Ningsih, Sri Susanti; Zulia, Cik (Program Studi Pendidikan Biologi, 2025)
ABSTRACT The study was conducted in Ujung Padang Village, Simalungun Regency, North Sumatra Province with a hot climate zone type, with an altitude of 25 m above sea level. The study was conducted in January - March 2025. The method applied in this study was a Randomized Block Design (RAK) with a factorial system that combines two main variables. The first factor is the irradiation time consisting of 3 levels, namely: Wo = 0 days, W1 = 15 days, W2 = 30 days. The second factor is the duration of irradiation consisting of 3 levels, namely: L0 = 0 hours, L1 = 6 hours, L2 = 12 hours. The observation variables of this study include the number of flower buds, number of flowers, number of fruits, fruit weight (kg).The results of this study indicate that the effect of time and duration of irradiation significantly affect the number of 2 week old dragon fruit flower buds, the number of dragon fruit flower buds per plot with the best treatment is at a duration of 15 days 6 hours (W1L1) with a total of 8.67 flower buds. The effect of time and duration of irradiation significantly affect the number of 4-week-old dragon fruit flowers, the number of dragon fruit flowers per plot with the best treatment is at a duration of 15 days 6 hours (W1L1) with a total of 14.67 flowers. The effect of time and duration of irradiation does not significantly affect the number of 6-week-old dragon fruit, the number of dragon fruit flowers per plot with the best treatment is at a duration of 15 days 6 hours (W1L1) with a total of14.67 fruits. The effect of time and duration of irradiation does not significantly affect the weight of 8-week-old dragon fruit, the weight of dragon fruit per plot with the best treatment is at a duration of 0 days 12 hours (W0L2) with a total of 5.87.